Assessing building-integrated bioremediation infrastructure within the context of unsustainable rising atmospheric CO2 - Phoebe Mankiewicz Ledins; Christina Ciardullo; Chunxu Huang; Patrick Pease; Tian Ma; Rebecca Rubright; Charlotte Welch; Michelle L. Bell; Nusrat Jung; Krystal J. Godri Pollitt; Elizabeth Hénaff; Anna Dyson (Energy and Buildings, 2026)

Prevalence of Food Insecurity and Association with Depression Among Graduate Students at an Urban University - K. Bell; A. Hollenbeck; M. Masters; J. Lunsford; L. Pollitt; K. Whitson; D. Mccutcheon (Journal of the Academy of Nutrition and Dietetics, 2023)

Trace analysis of per- and polyfluorinated alkyl substances (PFAS) in dried blood spots – Demonstration of reproducibility and comparability to venous blood samples - Elizabeth Z. Lin; Sara L. Nason; Alexander Zhong; John Fortner; Krystal J. Godri Pollitt (Science of The Total Environment, 2023)

Fluorescence in situ hybridization analysis of hindgut bacteria associated with the development of equine laminitis - Gabriel J. Milinovich; Darren J. Trott; Paul C. Burrell; Emma L. Croser; Rafat A. M. Al Jassim; John M. Morton; Andrew W. van Eps; Christopher C. Pollitt (Environmental Microbiology, 2008)

Fluorescence in situ hybridization analysis of hindgut bacteria associated with the development of equine laminitis - Gabriel J. Milinovich; Darren J. Trott; Paul C. Burrell; Emma L. Croser; Rafat A. M. Al Jassim; John M. Morton; Andrew W. Van Eps; Christopher C. Pollitt (Environmental Microbiology, 2007)
Summary Carbohydrate‐induced laminitis in horses is characterized by marked changes in the composition of the hindgut microbiota, from a predominantly Gram‐negative population to one dominated by Gram‐positive bacteria. The objective of this study was to monitor changes in the relative abundance of selected hindgut bacteria that have previously been implicated in the pathophysiology of equine laminitis using fluorescence in situ hybridization (FISH). Caecal cannulae were surgically implanted in five Standardbred horses and laminitis induced by oral administration of a bolus dose of oligofructose. Caecal fluid and faecal specimens were collected over a 48 h period at 2 to 4 h intervals post‐oligofructose administration and subjected to FISH using probes specific for nine bacterial groups to determine changes in their relative abundance compared with total bacteria hybridizing to the generic EUBMIX probe. Additionally, hoof biopsies were taken over the course of the experiment at 6 h intervals and evaluated for histopathological changes consistent with laminitis, allowing changes in hindgut microbiota to be correlated with the onset of lesions in the foot. Of the microorganisms specifically targeted, streptococci of the Streptococcus bovis / equinus complex were the only bacteria that consistently proliferated in both caecal fluid and faeces immediately before the onset of histological signs of laminitis. Furthermore, lactobacilli, Enterobacteriaceae , Allisonella histaminiformans , enterococci, Bacteroides fragilis , Mitsuokella jalaludinii and Clostridium difficile did not establish significant populations in the hindgut before the onset of equine laminitis.

Changes in equine hindgut bacterial populations during oligofructose‐induced laminitis - G. J. Milinovich; D. J. Trott; P. C. Burrell; A. W. Van Eps; M. B. Thoefner; L. L. Blackall; R. A. M. Al Jassim; J. M. Morton; C. C. Pollitt (Environmental Microbiology, 2006)
Summary In the horse, carbohydrate overload is thought to play an integral role in the onset of laminitis by drastically altering the profile of bacterial populations in the hindgut. The objectives of this study were to develop and validate microbial ecology methods to monitor changes in bacterial populations throughout the course of experimentally induced laminitis and to identify the predominant oligofructose‐utilizing organisms. Laminitis was induced in five horses by administration of oligofructose. Faecal specimens were collected at 8 h intervals from 72 h before to 72 h after the administration of oligofructose. Hindgut microbiota able to utilize oligofructose were enumerated throughout the course of the experiment using habitat‐simulating medium. Isolates were collected and representatives identified by 16S rRNA gene sequencing. The majority of these isolates collected belonged to the genus Streptococcus , 91% of which were identified as being most closely related to Streptococcus infantarius ssp. coli . Furthermore, S . infantarius ssp. coli was the predominant oligofructose‐utilizing organism isolated before the onset of lameness. Fluorescence in situ hybridization probes developed to specifically target the isolated Streptococcus spp. demonstrated marked population increases between 8 and 16 h post oligofructose administration. This was followed by a rapid population decline which corresponded with a sharp decline in faecal pH and subsequently lameness at 24–32 h post oligofructose administration. This research suggests that streptococci within the Streptococcus bovis / equinus complex may be involved in the series of events which precede the onset of laminitis in the horse.